Mathematics in the Sandbox: Investigating Spontaneous Mathematical Talk During Free Play - Diana Putri Prahasti; Muhammad Furqon; Vivi Anggraini; Fachri Aldin; Qisthi Efridita (Al-Qalam Institute, 2026)
Children often explore mathematical ideas naturally while playing, yet these moments are rarely captured in early childhood classrooms. The purpose of this research is to investigate how spontaneous mathematical talk emerges during free play in a sandbox environment and to understand the types of mathematical ideas children express. A qualitative observational approach was used to document children’s conversations and interactions during unstructured sandbox play. Data were collected through field observations and audio recordings of children’s dialogue while they built, measured, compared, and organized materials in the sand. The recorded interactions were then coded and analyzed to identify patterns of mathematical language and concepts. The findings show that children frequently used informal mathematical talk such as counting, comparing sizes, estimating quantities, and describing shapes while collaborating with peers. These conversations appeared naturally without direct instruction and often emerged when children negotiated roles, shared materials, or solved small problems during play. The study suggests that free play spaces can become rich contexts for early mathematical thinking. Recognizing and supporting these moments may help educators encourage mathematical language in more natural and meaningful ways during everyday classroom activities.